2021
DOI: 10.1017/ipm.2021.1
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pandemic: influence of relationship status on stress, anxiety, and depression in Canada

Abstract: Objective: To examine the impact of relationship status on levels of stress, anxiety, and depression during the COVID-19 pandemic, to identify the relationship groups who are at greater risk, thereby facilitating channelling of appropriate support to these individuals. Methods: The sample was drawn from individuals who subscribed to the Text4Hope program, a cognitive behavioural therapy inspired text messaging service developed to support Albertans during the COVID-19 pandemic. A survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
22
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 49 publications
(55 reference statements)
10
22
0
2
Order By: Relevance
“…In the present study, satisfaction with finances, relationships, and housing proved relevant for DAS, as predicted. Considering the known association of personal conflicts and dissatisfaction with close relationships as a relevant predisposing factor in mood and anxiety symptoms ( 43 ), participants in unstable relationships showed higher levels of depression and anxiety than those in stable relationships ( 44 ), and satisfaction in partnership reduced the risk of depression and anxiety ( 45 , 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, satisfaction with finances, relationships, and housing proved relevant for DAS, as predicted. Considering the known association of personal conflicts and dissatisfaction with close relationships as a relevant predisposing factor in mood and anxiety symptoms ( 43 ), participants in unstable relationships showed higher levels of depression and anxiety than those in stable relationships ( 44 ), and satisfaction in partnership reduced the risk of depression and anxiety ( 45 , 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety levels were higher among married individuals in the present study compared to unmarried participants. In a study from Canada investigating the effect of Covid-19, Nkire et al (2020) determined high levels of anxiety and depression in single individuals [21]. Özdin & Bayrak Özdin 2020 and Passos et al (2020) both found no difference in anxiety in terms of marital status [19,22].…”
Section: Discussionmentioning
confidence: 99%
“…to have some close, trusted person around is a protective factor. In contrast being alone and low levels of social support lead to higher levels of fear and other mental health issues [ 28 ].…”
Section: Discussionmentioning
confidence: 99%